THE MANAGEMENT OF HUMAN RESOURCE TRANSFORMATION OF RANGER SECURITY GUARD INVESTIGATION CO., LTD - Thongthip, Boonruen; Kulbutra, Weerapol (Journal of MCU Nakhondhat, 2020)
This research has the objective: To study problems and factors of human resource change management as well as find suggestions and guidelines to draw capacity in human resource change management Out to make the most of every aspect the sample used in this research was the executives and employees of the Rangers Investigation Co., Ltd. using a mixed research methodology. The quantitative research of 3 groups, total 628 sets, accounted for 100%. Questionnaires were submitted using google form. The results were analyzed by the SPSS V.26 program and analyzed by percentage, mean, standard deviation. One - way variance Dual Mean Qualitative research section In - depth interviews consisted of 15 people in 3 groups using in - depth interviews. And use of content analysis techniques for context the research study found that Problems and changing factors are habitat and environment. If it is not suitable, it will reduce physical performance until it is not ready to perform duties, which will repeat endlessly. And in terms of rights and fairness There must be penalties that are appropriate and practical. And guidelines and recommendations for managing changes in human resources should develop a quality of life development plan to lead to the effectiveness of the organization in terms of performance. And the development of efficiency in response to all customer needs in a timely manner, the Company places great importance on the management process of human resource change of security companies such as meeting customers. Complaints via e-mail, website and the development of the efficiency of the security personnel to have specific knowledge on organizational culture according to the situation of the company’s customers.